Development of an Automated Cost Control System in Contractors Firms - Ali, Khalid Abdelghafar (2000)
There are still widespread use of papers as a medium to capture and exchange of information among participants in construction cost control process. Although there is a relatively little use of automation tools, there is a distinct word processing environment formats. Each package creates its own data files in different formats resulting in difficulties with exchanging data electronically. These difficulties lead to inefficient flow of information to control cost, and some feedback problems among sites and across organizational boundaries. This negatively affects the availability of cost historical database as well as data from projects at hand. This implies that, it is time to automate cost control to achieve some kind of uniformity and standardization. To effectively achieve this, one specific IT tool, namely shared databases through data accessibility capability, has been used. The automated cost control has been developed using the Entity-Relationship modeling (ERM) methodology. It started with a formal definition for the problem, and conceptually been designed. Then a logical refinement for the conceptual model is developed that lead to the physical implementation of the system. The resulted system. The resulted cost control system has been developed in a formal and systematic manner. It has used Microsoft Access as a target database Management System (DBMS), under windows environment. In addition, the cost control system has the capabilities to prepare cost reports, undergo different types of queries with users and update data. The cost control system described in this research represents a significant contribution in construction cost control, since it satisfies the condition of uniformity under windows environment. It is easy to use, since the user can interface it by just 'point and click', as it uses Query-By-Example (QBE) language.